2019
DOI: 10.1029/2019gl084620
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamics of Saturn's Main Aurorae

Abstract: Saturn's main aurorae are thought to be generated by plasma flow shears associated with a gradient in angular plasma velocity in the outer magnetosphere. Dungey cycle convection across the polar cap, in combination with rotational flow, may maximize (minimize) this flow shear at dawn (dusk) under strong solar wind driving. Using imagery from Cassini's Ultraviolet Imaging Spectrograph, we surprisingly find no related asymmetry in auroral power but demonstrate that the previously observed “dawn arc” is a signatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 92 publications
0
24
0
Order By: Relevance
“…Recently, Bader et al (2019) used images of the northern aurora from the Cassini's Ultraviolet Imaging Spectrograph to show that the median auroral power has no dawn‐dusk asymmetry. They show the “dawn arc” is seemingly a transient signature of large‐scale dynamics in the magnetotail, namely, reconnection down tail in the tail current sheet, followed by plasma injection near dawn, which affects the mean auroral power.…”
Section: Discussion Of the Difference In Ppo‐independent Upward Currentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Bader et al (2019) used images of the northern aurora from the Cassini's Ultraviolet Imaging Spectrograph to show that the median auroral power has no dawn‐dusk asymmetry. They show the “dawn arc” is seemingly a transient signature of large‐scale dynamics in the magnetotail, namely, reconnection down tail in the tail current sheet, followed by plasma injection near dawn, which affects the mean auroral power.…”
Section: Discussion Of the Difference In Ppo‐independent Upward Currentsmentioning
confidence: 99%
“…One must be cautious of simply relating current density with auroral emission power. Since Bader et al (2019) shows that dawn‐dusk asymmetry is due to transient signatures of magnetotail reconnection, one would expect that the auroral electron source population will change due to these events, which could lead to a hotter/more tenuous plasma. This was shown by Hunt et al (2016) to give an increased precipitating energy flux for fixed current parameters.…”
Section: Discussion Of the Difference In Ppo‐independent Upward Currentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Equatorward bifurcations from the main auroral emission at later local times may also map to areas of active interchange in the magnetosphere, triggered as the source region plasma drifts inward and disperses (e.g., Radioti et al, ). A recent survey of Cassini Ultraviolet Imaging Spectrograph (UVIS) data has confirmed that Saturn's dawnside auroras are dominated by bright, transient features rotating through the sector, likely following large‐scale injection events (Bader et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The dawnside is usually characterized by a narrow arc which, while essentially always present, shows significant variations in latitude and intensity. The latitudinal variation is thought to be controlled by the amount of open flux contained in the polar cap, by periodic displacements due to PPO FACs and by solar activity (e.g., Badman et al, , ; Cowley et al, ; Bader, Badman, Kinrade, et al, ); the variation in intensity is less understood but seems to be influenced by solar wind conditions and PPO current systems overlaid with different transient signatures resulting from dynamic events in the magnetosphere (e.g., Bader, Badman, Cowley, et al, ). This auroral arc is thought to correspond to the layer of upward FAC seen in in situ field data in the same LT sector, which is located about 1° equatorward of the open‐closed field line boundary and may be related to a subcorotation flow shear modulated by conductivity gradients (Hunt et al, ; Bradley et al, ).…”
Section: Dawn‐dusk Asymmetries Of the Main Auroraementioning
confidence: 99%